Na roda do conhecimento: entre saberes da capoeira e saberes da escola. - Pertussatti, Marcelo (2018)
This bibliographic and qualitative research investigates possible pedagogical and epistemological relationships between Capoeira wisdom and school knowledge in school. The investigation starts from a Literature Review of the educational possibilities of Capoeira in the school, from the reading of theses, dissertations and articles accessed on BDTD-IBICT and CAPES research portals, as well as from other literatures in physical and digital media (units of analysis). The method of study used is Bardin's (2016) Content Analysis (Análise de Conteúdo – AC), which has 5 steps: 1) organization of the analysis; 2) coding, 3) categorization, 4) inference, and 5) data processing / interpretation. The research is developed in 4 (four) chapters. In chapter I is made a philosophical problematization of the subject, by contextual data from empirical and subjective experience of the researcher, by history aspects of Capoeira, by contemporary researches that approaches Capoeira in an educational dimension, and, finally, about the method of study. In Chapter II it’s investigated about knowledge present in the context of Capoeira, with a delimitation of content analysis about researches developed by Abib (2004) and Heine (2010), through which, relations among ways of popular culture wisdom transmitting, scientific knowledge and Capoeira wisdom are evidenced. In Chapter III the research is about knowledge present in School, with the delimitation of content analysis on Lopes, A.R.C. (1999) and Brazil/MEC/BNCC (2017), focusing on post-critical studies of curriculum theories, from Popkewitz, T.T. da Silva, Moreira, A.R.C. Lopes and Macedo; and by Brasil/MEC/BNCC, Cunha and A.R.C Lopes, Aguiar and Dourado. In Chapter IV, a dialogue between Capoeira wisdom and school knowledge is developed, in the continuity of the post-critical curricular debate, with the contribution of cultural studies by Hall, Bauman, Moreira and Candau; with the reflection of Neira and Nunes and of a Collective of Authors on the corporal culture in the curriculum of the school physical education; besides legislation and official documents concerning Capoeira themes (units of context). It was inferred with this study that the approach of the educational theme of Capoeira in the school has a multidisciplinary character; that the educational focus of Capoeira in master's and doctoral research in the last two decades have been increased; that there has been an expansion of Capoeira teaching in formal educational spaces such as schools and universities; that Capoeira has a multidimensional and multicultural character; that the presence of Afro-Brazilian wisdom of Capoeira's popular culture in the schooling curriculum, interrelated to the scientific and daily knowledge of the school, can be great opportunity to foster processes of identity affirmation, ethnic-racial respect, patrimonial and intercultural education in schools; and that the wisdom of Capoeira are identified as educational and school knowledge.